SOSIALISASI PENGELOLAAN SAMPAH BERBASIS 3R DI DESA COT MANCANG ACEH BESAR - Nanda Desreza; Safrina; Nur Azizah Rahmatika; Dina Maulina; Luthfiyyah Mumtazah; Raihan Kamila; Zora Ismunawaddah; M. A. Hafizh Alhilal; Andika Saputra (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
The 3R-based waste management (reduce, reuse, recycle) carried out by children in Cot Mancang Village, Aceh Besar, has significant potential for replication elsewhere, thus requiring an in-depth study of its implementation. This community service aims to identify the social characteristics and participation capacity of children in Cot Mancang Village in waste management. It analyzes the children's perceptions of the health benefits of proper waste management. The service employs an educational approach and observation involving 20 school-aged children. The objectives of the service are to measure the level of understanding of children in Cot Mancang Village both before and after the socialization and to provide materials related to waste management. The results of the service show an improvement in the understanding of waste management among the children in Cot Mancang Village. This improvement is evident from the pre-test and post-test results conducted before and after the socialization. In conclusion, it is clear that socialization regarding waste management can enhance the children's understanding of proper waste management.